SYNTHESIS OF ZINC SULFIDE AND ZINC-IRON SULFIDE NANOPARTICLES FROM ZINC(II) DITHIOCARBAMATE COMPLEXES AND THEIR UTILITY FOR PHOTOCATALYTIC DEGRADATION OF DYES - G. Gurumoorthy (International Journal of Modern Agriculture, 2020)
Bis(N-(pyrrol-2-ylmethyl)-N-(2-phenylethyl)dithiocarbamato-S,S′)zinc(II) (1) and bis(N-methylferrocenyl-N-(2-phenylethyl)dithiocarbamato-S,S′)zinc(II) (2) have been synthesized. Complexes 1 and 2 have been used as precursors for the preparation of zinc sulfide and zinc-iron sulfide nanoparticles. Morphological characterization of nanoparticles was carried out using TEM. The nanoparticles are explored as photocatalysts to study the degradation of dyes using methylene blue and rhodamine-B in aqueous solution under UV irradiation. The zinc-iron sulfide works as an efficient photocatalyst for degradation of rhodamine-B